Demokrasi dalam Pendidikan Islam - Raudatul Janna; Kasful Anwar; Sya’roni Sya’roni (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This paper discusses democracy in Islamic education, this paper aims to understand in depth the nature of educational democracy, namely educational democracy is a view that prioritizes obligations and rights, feelings and treatment by educational staff towards students in the educational process which includes 3 things, namely: respect for the dignity of fellow human beings, every human being has a change towards a healthy mind, and is related to common interests and welfare. Islamic educational democracy is the principle of implementing Islamic democracy in Islamic education. The democratic form of Islamic education is as follows: freedom for educators and students. Freedom here includes: (1) freedom to work; (2) freedom to develop potential; (3) freedom of opinion, equality for students in Islamic education, and respect for individual dignity in Islamic education. Next, to find out the democratic implementation of Islamic education through Integralistic education, Humanistic education, Pragmatic education, education that is abolished in Culture. The problem of democracy in Islamic education. The fundamental problem of Islamic education is the lack of clarity in the Islamic education paradigm. The ideological paradigm and the scientific paradigm are mixed in such a complex way that the scientific ideological paradigm develops. As a result, the tradition of creative, dynamic and open scientific thinking in the Islamic tradition, as well as the essence of revelation, is really difficult to develop. Democratic solutions in Islamic education: Changes that need to be made in Islamic education, namely emphasizing that Islamic educational institutions must design alternative, more democratic educational models that are in line with current development needs. The research method used is a basic theory method that uses data from materials that are library research, where the author reads and studies books or literature related to the problem being studied.